2008
DOI: 10.1021/cm801534a
|View full text |Cite
|
Sign up to set email alerts
|

Hexagonal YFe1−xPdxO3−δ: Nonperovskite Host Compounds for Pd2+ and Their Catalytic Activity for CO Oxidation

Abstract: Metastable YFeO 3 with the hexagonal YAlO 3 structure was obtained by a sol-gel process at 700 °C, using metal nitrate precursors with pH control and the appropriate citric acid to nitrate ratio. Under similar conditions, YFe 1-x Pd x O 3-δ (0 < x e 0.1) compositions were also prepared. The substitution of Fe by Pd stabilizes the YAlO 3 structure at higher temperatures. The crystal structures of YFe 1-x Pd x O 3-δ (0 e x e 0.1) were refined by Rietveld analysis of X-ray and neutron powder diffraction data. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
98
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(100 citation statements)
references
References 33 publications
2
98
0
Order By: Relevance
“…On reduction with hydrogen, Pd particles segregated from the perovskite lattice, as confirmed by the H 2 -TPR, XPS, and HRTEM measurements, and were more active for CO oxidation than were the PdO species within the perovskite lattice, lowering the T 50 by 40 K. A similar phenomenon has been observed for LaCo 0.95 Pd 0.05 O 3 : reduction with hydrogen at 453 K lowered the T 50 by 43 K in CO oxidation [6]. In contrast, the activity for CO oxidation decreased on a BaCe 0.90 Pd 0.10 O 3 perovskite [9] and was almost unaffected on a YFe 0.90 Pd 0.10 O 3 perovskite [10] on reduction with hydrogen at high temperatures. For comparison, CO oxidation was tested on the reference Pd/ LaFeO 3 catalyst.…”
Section: Co Oxidationsupporting
confidence: 69%
See 3 more Smart Citations
“…On reduction with hydrogen, Pd particles segregated from the perovskite lattice, as confirmed by the H 2 -TPR, XPS, and HRTEM measurements, and were more active for CO oxidation than were the PdO species within the perovskite lattice, lowering the T 50 by 40 K. A similar phenomenon has been observed for LaCo 0.95 Pd 0.05 O 3 : reduction with hydrogen at 453 K lowered the T 50 by 43 K in CO oxidation [6]. In contrast, the activity for CO oxidation decreased on a BaCe 0.90 Pd 0.10 O 3 perovskite [9] and was almost unaffected on a YFe 0.90 Pd 0.10 O 3 perovskite [10] on reduction with hydrogen at high temperatures. For comparison, CO oxidation was tested on the reference Pd/ LaFeO 3 catalyst.…”
Section: Co Oxidationsupporting
confidence: 69%
“…The magnified XRD patterns of the most intense (121) reflections showed that the 2h positions in the range 32.08-32.10°remained unchanged from 473 to 1,073 K, suggesting that Pd segregation from the perovskite framework did not obviously alter the perovskite structure. [10], and LaFePd 0.05 O 3 [11]. The Pd species located at the perovskite lattice [9,10] or dispersed on the perovskite surface [11] were considered to be the active sites for CO oxidation.…”
Section: Co Oxidationmentioning
confidence: 99%
See 2 more Smart Citations
“…Li et al have studied the CO oxidation activity of h-YFe 1¹x Pd x O 3¹¤ obtained by calcination of the precursor synthesized by a sol gel process. 13) In a previous paper, we compared the catalytic activities of o-and h-YbFeO 3 phases and found that the h-YbFeO 3 sample, which had a high surface area (29 m 2 g ¹1 ) even after calcination at 800°C, had a higher catalytic activity for methane combustion than the o-YbFeO 3 sample calcined at 800°C. 14) In this work, properties of h-and o-YbFeO 3 samples for the supports of the noble metal catalysts were examined: combustion reactions of propane or propene on these catalysts were investigated.…”
Section: Introductionmentioning
confidence: 97%